Home gardens of Central Asia: Reservoirs of diversity of fruit and nut tree species - Vinceti, Barbara; Elias, Marlène; Azimov, Rashid; Turdieva, Muhabbat; Aaliev, Sagynbek; Bobokalonov, Farhod; Butkov, Evgeniy; Kaparova, Elmira; Mukhsimov, Nurullo; Shamuradova, Svetlana; Turgunbaev, Kubanichbek; Azizova, Nodira; et al. (2022)
Central Asia is an important center of origin for many globally valued fruit and nut tree species. Forest degradation and deforestation are cause for concern for the conservation of these valuable species. Home gardens have the important function of sustaining household food consumption and income generation, and can play a critical role in conserving the diversity of fruit and nut trees. The dataset includes interviews with farmers who maintain home gardens to understand the diversity of tree species and varieties that they maintain, the sources of tree planting material they use, and their motivations for maintaining home gardens in future. The main variables studied are presented in dedicated Excel files. Methodology: Structured interviews